2018
DOI: 10.1007/s11095-017-2324-y
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Engineered PAMAM Dendrimers as Nanoconstructs for the Enhanced Anti-Cancer Potential and Improved In vivo Brain Pharmacokinetics of Temozolomide

Abstract: The attractive ex vivo cytotoxicity against two glioma cell lines; U-251 and T-98G and phase solubility studies of TMZ revealed remarkable results. In vivo studies of prepared nanoformulation were significant and promising that explored the double concentration of TMZ in brain due to surface functionality of dendrimer. The reported work is novel and non- obvious as none of such approaches using chitosan anchored dendrimer for TMZ delivery has been reported earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…The nanoparticle improved the cytotoxic activity of sirolimus against human cancer cell lines. In another study of polyamidoamine-chitosan (PCT) carrying temozolomide, promising pharmacokinetic profiles were reported with improved AUC (1.2-fold) and prolonged t 1/2 (1.5-fold) compared with free drug 33…”
Section: Resultsmentioning
confidence: 99%
“…The nanoparticle improved the cytotoxic activity of sirolimus against human cancer cell lines. In another study of polyamidoamine-chitosan (PCT) carrying temozolomide, promising pharmacokinetic profiles were reported with improved AUC (1.2-fold) and prolonged t 1/2 (1.5-fold) compared with free drug 33…”
Section: Resultsmentioning
confidence: 99%
“…Undoubtedly it can be said that transport systems for cancer drugs based on dendrimers are the most studied and published [113][114][115][116][117][118]. This high interest is due to its versatility to mold them to the need of the system under study.…”
Section: Dendrimer As Drug Delivery Systems To Cancer Treatmentsmentioning
confidence: 99%
“…Chitosan-coated PAMAM conjugated to TMZ improved GBM tumor targeting in U-251 and T-98G cell lines at lower TMZ concentrations. In vivo pharmacokinetics exhibited sustained release with a half-life of 22.74 h in chitosan-coated dendrimer compared to free drug (TMZ alone) at 15.35 h. Reported work revealed that chitosan-anchored nanoparticles are sufficient at delivering chemotherapy across the BBB and enhanced tumor cell cytotoxicity ex vivo ( 67 ).…”
Section: Chitosan-based Delivery-systems To Brain Cancermentioning
confidence: 99%